A Social Development Saga : India Uttar Pradesh Basic Education and India District Primary Education Projects - Kuehnast, Kathleen (World Bank, Washington, DC, 2012)
The Uttar Pradesh (UP) Basic Education Pilot Project and the national India District Primary Education Project exemplify good social development practices. The pilot project in UP to assist girls to achieve better education proved so successful that it was scaled up to a national project. The guiding principle of both projects is to improve education by building capacity at the community level. preparation. Surveys and focus group discussions identified a wide-range of educational issues at the village level. Problems ranged from caste discrimination to debate on the language of instruction to the impact of weather on educational opportunities. In some villages, girls were not attending school because of their responsibility to care for younger siblings. In other places, the issue was girls' safety. Lessons learned included the following: 1) Community support for education is a central element of a successful school development program. 2) Community implementation is a cost-effective way to achieve large-scale school construction. 3) Block Resource Centers and Cluster Resource Centers can serve as effective mechanisms to provide recurrent in-service training and school-based professional support for teachers. 4) Improving the quality of education and strengthening institutional capacity are long-term processes. 5) Micro-planning is necessary to assess the need for new schools and additional classrooms and teachers.